2017
DOI: 10.5455/javar.2017.d238
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular detection of the causal agents of sub-clinical mastitis in dairy cows in Sirajganj and Pabna districts, Bangladesh

Abstract: Objective: The present research work was undertaken with the objectives to investigate the prevalence and molecular detection of the causal agents of subclinical mastitis (SCM) in cows at milk shed areas in Sirajganj and Pabna districts, Bangladesh. Materials and methods: A total of 300 milk samples were randomly collected from Baghabari milk shed areas of Sirajganj and Pabna districts. The milk samples were subjected for California Mastitis Test (CMT) for identifying SCM. Total 81 positive samples were then u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…According to the present study, the prevalence of subclinical mastitis (SCM) was higher and this finding was sim-ilar in comparison to some previous findings. The current result was supported by Rahman et al (2014); Tripura et al (2014); Kabir et al (2017), who reported 50%-60% incidences of SCM in dairy cows on bacteriological examination. The finding of the present study was also supported by Kader et al (2002), who reported a 46.6 % prevalence of SCM in Bangladesh but the results disagreed with the findings of Rahman et al (2010).…”
Section: Discussionsupporting
confidence: 78%
“…According to the present study, the prevalence of subclinical mastitis (SCM) was higher and this finding was sim-ilar in comparison to some previous findings. The current result was supported by Rahman et al (2014); Tripura et al (2014); Kabir et al (2017), who reported 50%-60% incidences of SCM in dairy cows on bacteriological examination. The finding of the present study was also supported by Kader et al (2002), who reported a 46.6 % prevalence of SCM in Bangladesh but the results disagreed with the findings of Rahman et al (2010).…”
Section: Discussionsupporting
confidence: 78%
“…Although the provision of SCC is readily available to most dairy farms in developed countries on a monthly basis through the dairy herd improvement (DHI) program, this practice yet not accustomed in Bangladesh. Because of the high prevalence (30-72%) of SCM and abundance of the mastitis pathogens [14][15][16][17][18][19], the provision of SCCs for routine SCM screening in dairy herds will be of great benefit in reducing the occurrence of SCM and ensuring milk quality as well.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, specific enriched media were used for the isolation and identification of Salmonella spp. which was also used by a number of researchers such as (Kabir et al, 2017). The morphology of the isolated Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%